Thoughts on health economics in rheumatoid arthritis - Kobelt, Gisela (BMJ Group, 2007)
In this manuscript we discuss the reasons why and how health economics is important, the type of economic studies that are relevant in healthcare to different stakeholders in general, and what analyses can and have been performed in the field of rheumatoid arthritis (RA). We will thus specifically address costs and outcome measurements in RA, as well as the need for modelling in chronic progressive diseases.